Lysolecithin, but not lecithin, improves nutrient digestibility and growth rates in young broilers. Issue 4 (3rd July 2020) - Wealleans, A. L.; Buyse, J.; Scholey, D.; Van Campenhout, L.; Burton, E.; Di Benedetto, M.; Pritchard, S.; Nuyens, F.; Jansen, M.
ABSTRACT: 1. The potential of lecithin and lysolecithin to improve lipid digestion and growth performance was investigated in three experiments: 1. an in vitro model that mimics the intestinal conditions of the chick, 2. a digestibility trial with chicks (5–7 days of age), and 3. a performance trial until 21 days of age. 2. In experiment 1, palm oil (PO), palm oil with lecithin (PO+L), and palm oil with lysolecithin (PO+LY) were subjected to in vitro hydrolysis and applied to Caco-2 monolayers to assess lipid absorption. 3. The in vitro hydrolysis rate of triglycerides was higher in PO+LY (k = 11.76 × 10 3 /min) than in either PO (k = 9.73 × 10 3 /min) or PO+L (k = 8.41 × 10 3 /min), and the absorption of monoglycerides and free fatty acids was highest (P < 0.01) for PO+LY. In experiment 2, 90 broilers were assigned to three dietary treatments: a basal diet with 4% palm oil, and the basal diet supplemented with either 250 ppm lecithin or lysolecithin. 4. ATTD of crude fat was higher in broilers supplemented with lysolecithin, but was lower in broilers supplemented with lecithin. DM digestibility and AMEn in birds supplemented with lysolecithin were significantly higher (3.03% and 0.47 MJ/kg, respectively). 5. In experiment 3, 480 broilers were randomly allocated to four dietary treatments: basal diet with soybean oil (2%), basal diet with lecithin (2%), soybean oil diet with 250 ppm lysolecithin, or lecithin oil diet with 250 ppm lysolecithin. 6. Lecithin diets significantly reduced weight at day 10 and 21 compared with soybean oil. However, the addition of lysolecithin to lecithin-containing diets significantly improved bird performance. 7. The results of these studies showed that, in contrast to lecithin, lysolecithin was able to significantly improve the digestibility and energy values of feed in young broilers.